Pengaruh Disiplin terhadap Kinerja Pegawai pada Kantor Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Maluku - Ida Hitimala; Normawati Normawati; Jeanly Waisapy (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This research investigates how employee discipline affects their performance at the Human Resources Development Agency of Maluku Province. Discipline is seen as a key driver that shapes employees’ attitudes, accountability, and professional conduct within the organization. Using a quantitative method, the study examines the link between discipline as the predictor and performance as the outcome. Results reveal that disciplined employees exhibit higher efficiency, adhere to organizational rules, and complete responsibilities reliably. The study emphasizes that fostering discipline is crucial for boosting individual performance and advancing overall organizational productivity, especially in government institutions where structured work behavior underpins effective service delivery.